2020
DOI: 10.2478/czoto-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Life Style on Safety and Work Efficiency

Abstract: Occupational health and safety nowadays is beginning to be seen in a multi-interdisciplinary way. Man's lifestyle also contributes to safety at work and work efficiency. The employee performs tasks at a specific place and time, however, this work is also affected by elements of private life. This paper deals with the impact of private life and lifestyle on human professional work in the areas of work safety and its efficiency. The research has been conducted on the basis of the opinions of employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Also, the high level of way of life is suggestive of the high extent of work in which one can be the kind of person he or she would like to be. This claim is in line with various authors (Day et al, 2019;Zyska & Kiriliuk, 2020) who mentioned that employers are increasingly implementing programs that assist employees' well-being both inside and outside the workplace. Schools provide a suitable environment for promoting healthy lifestyles, so there is a need for easily implemented and evidencebased interventions designed to do so.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Also, the high level of way of life is suggestive of the high extent of work in which one can be the kind of person he or she would like to be. This claim is in line with various authors (Day et al, 2019;Zyska & Kiriliuk, 2020) who mentioned that employers are increasingly implementing programs that assist employees' well-being both inside and outside the workplace. Schools provide a suitable environment for promoting healthy lifestyles, so there is a need for easily implemented and evidencebased interventions designed to do so.…”
Section: Resultssupporting
confidence: 86%
“…Employers are increasingly implementing programs that assist employees' health and well-being both inside the workplace and outside of it. The potential of the employee must be addressed holistically (Zyska & Kiriliuk, 2020). Schools provide a suitable environment for promoting healthy lifestyles, so there is a need for easily implemented, customized, evidence-based interventions designed to do so.…”
Section: Work Valuesmentioning
confidence: 99%
“…The elimination of this cause is difficult since it mainly relates to faults in design and ergonomic of the material factor (49.3%), incorrect operation of the material factor (24.4%) and material defects (19.9%), including mostly hidden defects (12.7%) [16]. Enterprises undertake many preventive measures minimizing the number of accidents at work as well as activities within the framework of "good practices" which may be an inspiration for other enterprises [19,20,21,22]. It can be noted that for several years that the number of accidents at work has been decreasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of stressors, the profession of a policeman ranks first among 47 professions selected for the study (Falkiewicz, 2018). After research by the Central Institute for Labor Protection -National Research Institute, over 90% of the surveyed policemen found work in the Police to be stressful, and over 50% -that work in the Police and the stress related to it, to a large extent affects family life and personal relationships (Falkiewicz, 2018;Holubova V., 2016;Jasiulewicz-Kaczmarek et al, 2015;Niciejewska and Obrecht, 2020;Zyska and Kiriliuk, 2020). Stress has many consequences.…”
Section: Introductionmentioning
confidence: 99%